High-temperature LTCC assembly and design of SiC BJT-based negative charge pump. Issue 2 (3rd April 2022) - Roy, Sajib; Faruque, Khandokar Asif; Abbasi, Affan; Mantooth, Alan
ABSTRACT: This paper describes the negative charge pump design in state-of-the-art SiC BJT technology along with its assembly on the LTCC module for extremely high-temperature applications. Kiln thermal oven is used to test the system at 500°C and evaluate the system's high-temperature performance. The charge pump design is separated into two sections: a diode-connected BJT charge pump and a cross-coupled RC oscillator. Commercially available NHT dielectric capacitors (390 pF) are used for both circuit sections. The designed LTCC module used DuPont™ 9k7 dielectric with gold metallization for routing traces. The oscillator output frequency varied from 35.7 kHz to 125 kHz across temperature for a fixed supply voltage of 11 V.